Roles of Registered Nurses and Dentists under Health Security Programs within Communities: A Comprehensive Review - Alhababi, Jafar Sadiq Mohsen; Ibrahim Ahmed Khabrani; Thamer Meshal Ghazi Alotaibi; Dr. Saqer Alqarni; Omar Yousef Alharbi; Talal Houmod ALi Almutairi; Tahrir Karim Aldhafiri; Nawal Ali Ezzei Refaei; Awatif Saad Alshammari (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background: <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">In ensuring community health security, there should be optimal systems capable of addressing not only general but also specialized health concerns, especially with regard to dental or oral health, which greatly influences general well-being. Conventional systems addressing particular concerns lack efficacy when it comes to addressing overall community safety, more so when there are public health threats or crises. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim: <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">The systematic review investigates the efficacy of combined nurse and dentist professional roles within community health security schemes with regard to their effectiveness on health outcomes, disaster preparedness, and management of chronic illness. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods: <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">A systematic search was conducted using PubMed, CINAHL, Scopus, Web of Science, and Cochrane Library databases for articles that were published between 2013 and 2025. Experimental/observational studies and qualitative studies that assessed interprofessional nursing and dental collaboration were included in this systematic review. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results: <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">There was evidence that interprofessional practice made large positive differences in early systemic disease identification using oral-systemic evaluation, control of chronic disease, and disaster response capabilities. Interprofessional practice between dental and other healthcare practitioners improved outcomes related to hemoglobin A1c, hospitalization rates, and improved outcomes related to oral health. Interprofessional practice was associated with more comprehensive healthcare delivery when done during an emergency response. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion: <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">The blending of nursing knowledge and dental knowledge promotes synergistic effects for community health security. For an effective implementation strategy for these two professions to combine their knowledge, interdisciplinary education, and electronic health records would therefore be ideal for future programs focusing on such integration.